Beta-Geometric Regression for Modeling Count Data on First Antenatal Care Visit (ANC) with Application - Zainab Al-Balushi; Amadou Sarr; M. Mazharul Islam (Journal of Biostatistics and Epidemiology, 2023)
Introduction: Although geometric distribution, which is a special case of Negative Binomial (NB) distribution, also belongs to the discrete family of distributions, little attention has been paid to modeling count data with the geometric distribution. There are many real-life phenomena that follow the geometric distribution with a constant probability of first success. However, in practice, the probability of the first success may vary from trial to trial, making simple geometric models unsuitable for modeling such data. In this paper, assuming that the probability of the first success follows a Beta distribution, we developed a Beta-geometric distribution and Beta-geometric regression for modeling the count data that follow the geometric distribution and illustrated the suitability of the model through application to the count data on time to first antenatal care (ANC) visit.